A fault tolerant Red-HI based load management policy for a distributed multimedia streaming system - Aybay, Işık; Shah, Mohammed Ahmed (Unavailable, 2008)
In this paper, a novel distributed fault tolerant end-to-end video streaming policy, based on a hierarchical system of servers, is proposed. The main objectives of this policy are to provide fault tolerance, and, increase the flexibility offered in the network to improve both the network resource utilization and user benefits. Another advantage of this policy is that it provides popularity-zone centric dynamic multimedia object placement. The load management and fault tolerance are achieved using Redundant Hierarchy (Red-HI) for the multimedia servers coupled with parent-only query flooding policy. © 2008 by Bo?aziçi University.
8th International Symposium on Computer Networks, ISCN'08 --
Keywords: Computer networks; Electric load management; Electric power plant loads; Hierarchical systems; Distributed multimedia; Fault-tolerant; Management policy; Multimedia object; Multimedia servers; Network resource utilization; Query flooding; User benefits; Fault tolerance